Large-Scale Construction Waste Mountain-Mounding Technology Based on the Project in Meibei Lake Scenic Area - Miao Kang; Xiongbin Guo; Shoufu Li; Jincheng Fan; Yufei Xu; Weiye Gu; Teng Wang (Advances in Civil Engineering)
In the backdrop of China’s rapid economic growth and urbanization, the surge in construction waste poses mounting disposal challenges. This study primarily focuses on in-depth research and exploration of construction waste recycling technologies. By repurposing towering heaps of construction debris into artificial landscapes, it achieves resource reutilization and waste reduction, bearing profound significance for environmental protection, and resource utilization. Taking the Xi’an Meibei Lake Scenic Area construction waste embankment project as a case study, experiments on the physical properties of soil-construction waste mixtures were conducted. A three-dimensional computational model of the site was established, and typical cross-sections were selected for the slope stability calculations and analysis. This was coupled with on-site measurements to validate the practicality and effectiveness of the technology. The successful execution of the project has demonstrated the reliability of this technology, offering significant potential for widespread application and serving as a crucial reference for the similar projects.